Risk factors for aggravated COVID-19 despite medical care after admission among Japanese patients: A Japanese association for infectious diseases COVID registry study - Itaru Nakamura; Yusuke Koizumi; Hideki Araoka; Hiroaki Hata; Takashi Miki; Yusuke Tanaka; Chie Kobayashi; Kazuyoshi Kawakami (PLoS ONE, 2025)
Background Limited data are available on COVID-19 outcomes in the Japanese population. During the Wuhan strain–dominant period, we investigated factors associated with clinical deterioration of COVID-19 despite inpatient medical care in Japan. Materials and methods This retrospective, multicenter cohort study used data from the Japanese Association for Infectious Diseases (JAID) COVID registry to identify risk factors for progression to severe disease after hospital admission. The study population included Japanese patients with a confirmed diagnosis of COVID-19 between January 2020 and March 2021. Baseline data included demographics, symptoms at disease onset and admission, and laboratory findings. Univariate and multivariate logistic regression models were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for each explanatory variable associated with disease aggravation. Multiple imputation was used to handle missing data. The predictive performance of two multivariate models—Model I (based on measurable clinical findings) and Model II (based on interview data)—was assessed using the area under the receiver operating characteristic curve (AUC). Results A total of 2,884 patients were enrolled across 36 institutions in Japan. After excluding 25 ineligible cases and 45 protocol deviations, 2,814 patients were included in the analysis. Multivariate analysis identified several independent risk factors for disease aggravation despite inpatient care, including admission early in the pandemic, older age, impaired consciousness, respiratory distress, elevated BMI, high body temperature, anemia, cholestasis, dehydration, and elevated γ-GTP and LDH levels. The AUCs were 0.8928 for Model I and 0.8862 for Model II, indicating strong discriminatory power. Conclusion This study identified key risk factors for COVID-19 progression despite inpatient medical care among Japanese patients. These findings underscore the importance of early risk stratification for patients at high risk of deterioration despite treatment and may inform preparedness strategies for future respiratory pandemics.